Comparison of glued platelet-rich fibrin membrane and noneugenol pack as periodontal dressings after gingival depigmentation - Megha Poojari; Monali Shah; Prasad Nadig (Journal of Indian Society of Periodontology)
Periodontal surgery often necessitates the use of a periodontal dressing to protect the surgical site and facilitate healing. Commonly used dressings, such as noneugenol packs, offer some benefits but have significant drawbacks, including plaque accumulation, a sensation of foreignness, and no significant impact on healing enhancement. On the other hand, platelet-rich fibrin (PRF) membranes are rich in growth factors, which can accelerate wound healing and tissue regeneration. However, their use is limited due to the need for suturing to stabilize the membrane. N-butyl cyanoacrylate is a tissue adhesive known for its hemostatic and bacteriostatic properties and effectiveness in moist environments, presenting a potential solution for PRF membrane stabilization without the need for suturing. This case report evaluates the use of PRF membrane in combination with N-butyl cyanoacrylate adhesive as an alternative to traditional noneugenol periodontal dressing.